Postembryonic development of the dorsal chaetotaxy in Seira dowlingi (Collembola, Entomobryidae); with an analysis of the diagnostic and phylogenetic significance of primary chaetotaxy in Seira - Soto-Adames, Felipe N. (Zootaxa, 2008)
Chaetotaxy is probably the most important character system used to diagnose species in Entomobryidae, but its use in studies of phylogenetic relationships of suprageneric taxa has been hampered by difficulties in identifying the homology of individual setae. Currently there is developmental information for three (Orchesella, Entomobrya sensu lato and Lepidocyrtus sensu lato) of the four largest groups of entomobryids. Seira is the only major genus for which the postembryonic development of the chaetotaxy has not been described. To fill this gap a complete description of the postembryonic development of the dorsal chaetotaxy of Seira dowlingi (Wray, 1953) is presented. Based on this description and by comparisons with up to 96 additional Seira species, it is suggested that the loss of second abdominal segment primary setae m4 and p4 (by transformation into scales during postembryonic development) is the only chaetotaxic character diagnostic for the genus. The posterior botriothricum (homologous to D3) on the fourth abdominal segment is absent only in S. (Afroseira) rowani Yosii, from South Africa. It is suggested that the presence of seta p3 and absence of p4 on the third abdominal segment support a more recent relationship between Seira and Lepidocyrtus/Pseudosinella than between Seira and Entomobrya sensu lato.